2021
DOI: 10.3390/foods10030643
|View full text |Cite
|
Sign up to set email alerts
|

Heart Images on Food Labels: A Health Claim or Not?

Abstract: Health claims on food labels are used by food manufacturers to inform consumers about the health effects of a product, and such claims can have notable effects on consumer preferences. According to regulatory definitions, health claims can be either worded or presented as images, but it is not clear under which conditions an image on a food label should be considered a health claim. This question has important practical implications, as the use of health claims is strictly regulated. The objective of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Since these credence attributes are not visible or measurable by consumers themselves, public and private organisations aim to reduce information asymmetry between those developing and selling produce and those citizens purchasing them by requiring adequate labelling [3]. When labels truthfully provide this type of information, they can be used by consumers to inform themselves and by producers to share their unique selling points [4]. Less trustworthy labelling, when food business operators mislead consumers with deliberate false information, is not considered in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Since these credence attributes are not visible or measurable by consumers themselves, public and private organisations aim to reduce information asymmetry between those developing and selling produce and those citizens purchasing them by requiring adequate labelling [3]. When labels truthfully provide this type of information, they can be used by consumers to inform themselves and by producers to share their unique selling points [4]. Less trustworthy labelling, when food business operators mislead consumers with deliberate false information, is not considered in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Digitalized static FOP food labels and their effects on healthy food-related behavior based on the articles included in this review are, to some degree, in line with the results of prior research identified in the literature review section. In our systematic review, eight articles did find differences in hypothetical choices [ 52 , 53 , 54 , 58 , 59 , 62 , 63 , 73 , 74 ], three articles did find difference in self-reports [ 63 , 65 , 71 ], while two articles did not find difference in self-reports [ 64 , 69 ] as a function of digitalized static FOP food labels. Based on the studies that were identified in the literature review, two articles did find differences in hypothetical choice [ 17 , 37 ], and two articles did find differences in self-reports [ 36 , 37 ] as a function of digitalized static FOP food labels.…”
Section: Discussionmentioning
confidence: 86%
“…Out of those, a total of 25 reports were excluded based on the final eligibility criteria, as 10 of the reports did not investigate FOP food labels as defined in this review, five of the reports did not investigate behaviors related to healthy foods, four of the reports did not investigate the dependent variable specified in this review, and one report did not use primary data collection. This resulted in a total of 30 articles included in this review [ 15 , 33 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of health claims were general non-specific and/or function claims. Later on, researchers exploited the 2015 dataset to investigate the use of gluten-free claims ( 63 ), heart images ( 61 ), and marketing to children ( 62 ). Studies identified several challenges of such poorly regulated marketing, which often promotes foods with questionable overall nutritional composition.…”
Section: The Exploitation Of Use Of Branded Foods Database In Nutrition Researchmentioning
confidence: 99%